Distinct pathways for zinc metabolism in the terrestrial slug Arion vulgaris - Martin Dvorak (Nature Portfolio, 2019)
Abstract In most organisms, the concentration of free Zn2+ is controlled by metallothioneins (MTs). In contrast, no significant proportions of Zn2+ are bound to MTs in the slug, Arion vulgaris. Instead, this species possesses cytoplasmic low-molecular-weight Zn2+ (LMW Zn) binding compound that divert these metal ions into pathways uncoupled from MT metabolism. Zn2+ is accumulated in the midgut gland calcium cells of Arion vulgaris, where they associate with a low-molecular-weight ligand with an apparent molecular mass of ~ 2,000 Da. Mass spectrometry of the semi-purified LMW Zn binding compound combining an electrospray ion source with a differential mobility analyser coupled to a time-of-flight mass spectrometer revealed the presence of four Zn2+-containing ion signals, which arise from disintegration of one higher MW complex resulting in an ion-mobility diameter of 1.62 nm and a molecular mass of 837 Da. We expect that the novel Zn2+ ion storage pathway may be shared by many other gastropods, and particularly species that possess Cd-selective MT isoforms or variants with only very low affinity to Zn2+.